Indigenous Construction Technologies in Flood-Prone Areas of Western Kenya - China, S. S.; Waswa, George; Kundu, P.M.; Omuterema, S.O. (My University, 2007)
Shelter and sanitation are essential for the well-being and development of most societies. The approach and technology for the provision of shelter and sanitation varies with the social, economic and environmental conditions of a place. Sanitation of places with piped water is different with places without piped water. Likewise, shelter technology for regions prone to earthquake is different from that for areas not prone to earthquake. The purpose of this study was to identify indigenous knowledge and technologies in post-disaster construction in the flood prone areas of Budalang’i, in western Kenya, with emphasis on shelter and sanitation. The study focuses on shelter systems such as; human living houses, food stores, and livestock shelters; and sanitation systems such as toilets, water wells and pans. The study considers social, physical and environmental conditions of the region. Baseline survey, and observation methods were used to determine the existing indigenous technologies. Interviews of key informants and direct observation methods were also used in the study. Identification and analysis of construction concepts in the area was done. The study recommends in-depth study of other indigenous technologies since are useful and easily sustainable in reconstruction phase of the disaster.
Keywords: indigenous technology; Shelter; Sanitation; Flood disaster